2009
DOI: 10.3989/gya.097008
|View full text |Cite
|
Sign up to set email alerts
|

Composición química de aceites de las variedades Arbequina y Empeltre cultivadas en regadío

Abstract: This study examines the composition of oils extracted from young olive trees of the Arbequina and Empeltre varieties grown with irrigation in the same farm throughout a period of three seasons. Quality parameters, Fatty acid composition, sterols, waxes and aliphatic alcohols were analyzed. Although the quality of oils of both varieties was that of extra virgin, varietal differences were found. The peroxide value and the content of total polyphenols were much higher in Empeltre, whereas stability was higher in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
23
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 6 publications
6
23
1
Order By: Relevance
“…Similar results were obtained by other researchers (Vekiari et al, 2010). Gracia et al (2009) showed values of oleic acid of 68.9% and 11.6% of linoleic acid in the "Arbequina" variety. On the other hand, Salvador et al (2001) studied the "Cornicabra" variety and they obtained values of 80.8% and 4.66% of oleic and linoleic acids, respectively, which are higher than those obtained in this assay.…”
Section: Fatty Acid Compositionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar results were obtained by other researchers (Vekiari et al, 2010). Gracia et al (2009) showed values of oleic acid of 68.9% and 11.6% of linoleic acid in the "Arbequina" variety. On the other hand, Salvador et al (2001) studied the "Cornicabra" variety and they obtained values of 80.8% and 4.66% of oleic and linoleic acids, respectively, which are higher than those obtained in this assay.…”
Section: Fatty Acid Compositionsupporting
confidence: 91%
“…In this sense, oils from the "Carrasqueña" variety with higher ratios are those which showed higher values in oxidative stability (Table 1), while oils from the "Morisca" variety which had less oxidative stability, presented ratios of oleic/ linoleic of about 40% lower than the "Carrasqueña" variety. Some researchers (Aguilera et al, 2005;Gracia et al, 2009;Vekiari et al, 2010) demonstrated the importance of that relationship in the nutritional quality of the oil and its oxidative stability. This fact was corroborated with the oxidative susceptibility parameter which was assessed by the formula (m + (45 × L) + (100 × Ln), where m = % monounsaturated fatty acids, L = % linoleic acids and Ln = % linolenic acids) (Gracia et al, 2009).…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sterol composition in olive oil is affected by cultivar, crop year, geographic factors, degree of fruit ripeness, storage time of fruits prior to oil extraction, and processing (Boskou et al, 2006). The cultivars with the highest Δ 5 -avenasterol content are Koroneiki (23.9%) (Vekiari et al, 2010), Arbequina (23.2%) (Gracia et al, 2009), and Leccino (21.4%) (Gül and Seker, 2006). Accordingly, the high Δ 5 -avenasterol levels in the selection UC-I-2-35, observed in both years of the experiment (Figure 1), are exceptional within olive oil cultivars.…”
mentioning
confidence: 82%
“…Accepted: 27-01-12 commercial yields 3 years after planting and has yearly good production (de la . In addition, oil produced from Arbequina olives has excellent quality characteristics (Vossen, 2007;Gracia et al, 2009). We present the results of a study on the process of olive ripening in an experimental hedgerow orchard in Zaragoza.…”
Section: Introductionmentioning
confidence: 99%